Molecular detection of haemoparasites and characterization of Theileria parva from cattle in Mashonaland East Province, Zimbabwe - Marufu, Munyaradzi Christopher (University of Pretoria, 2023)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2022.